2018
DOI: 10.14254/2071-8330.2018/11-4/10
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of islamic banking adoption across different religious groups in Ghana: A panoptic perspective

Abstract: This study sought to ascertain critical determinants of Islamic Banking (IB) adoption among different religious groups. The study draws on from the Theory of Planned Behaviour, Diffusion of Innovation, Theory of Reasoned Action and Technology Acceptance Model on IB adoption. The study employed a quantitative research paradigm to study 600 individual financial service users in Ghana. Structured questionnaire from previous studies was adopted, modified and used to conveniently elicit data from the participants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 63 publications
(91 reference statements)
1
13
0
4
Order By: Relevance
“…Finally, it was emphasized that developing Shariah-compliant services is a major avenue for service innovation in Islamic banking, but policymakers, bankers and legislators need to come up with a common understanding to develop effective legal infrastructures and compliance measures. This is in line with the findings of Su'un et al (2018), who ascertain the growing prevalence of Islamic banking products such as Mudaraba (the sharing of profit and loss), Wadiah (safekeeping), Musharaka (joint ventures), etc., because of their significant impact on the welfare of both Islamic and non-Islamic communities.…”
Section: Findings and Discussionsupporting
confidence: 90%
“…Finally, it was emphasized that developing Shariah-compliant services is a major avenue for service innovation in Islamic banking, but policymakers, bankers and legislators need to come up with a common understanding to develop effective legal infrastructures and compliance measures. This is in line with the findings of Su'un et al (2018), who ascertain the growing prevalence of Islamic banking products such as Mudaraba (the sharing of profit and loss), Wadiah (safekeeping), Musharaka (joint ventures), etc., because of their significant impact on the welfare of both Islamic and non-Islamic communities.…”
Section: Findings and Discussionsupporting
confidence: 90%
“…However, other factors such as Islamic bank reputation, convenient and cost benefits are the most significant factor in determining whether customers will choose Islamic or vice versa. In contrast, using a panoptic approach, Su’un et al (2018) highlighted that, in the context of Ghana, the patronization of Muslims, Christians, African Traditional Religion (ATR) towards Islamic banks are mainly contributed by perceived knowledge, perceived benefit, innovativeness, religious factor customer’s attitude and readiness to comply with Shariah. From the marketing perspectives, using questionnaire-based analysis and a convenience sample of 474 respondents from Jakarta, Bogor and Depok, Wu et al (2019) findings revealed that trust and satisfaction are the main drivers of customer’s loyalty in Indonesian Islamic banking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, others think that Islamic banking services will soon dominate the development of banking in Asian countries. Despite this decisive dominance, efforts to increase understanding for non-Muslim customers need to be increased in the future Su'un et al (2019). argues that differences between Muslim and non-Muslim religious leaders are seen in religious affiliation and commitment as a segmentation strategy.…”
mentioning
confidence: 99%